Extended-spectrum β-lactamase-encoding genes are spreading on a wide range of Escherichia coli plasmids existing prior to the use of third-generation cephalosporins. Issue 9 (6th August 2018) - Branger, Catherine; Ledda, Alice; Billard-Pomares, Typhaine; Doublet, Benoît; Fouteau, Stéphanie; Barbe, Valérie; Roche, David; Cruveiller, Stéphane; Médigue, Claudine; Castellanos, Miguel; Decré, Dominique; Drieux-Rouze, Laurence; et al.
Abstract : To understand the evolutionary dynamics of extended-spectrum β-lactamase (ESBL)-encoding genes in Escherichia coli, we undertook a comparative genomic analysis of 116 whole plasmid sequences of human or animal origin isolated over a period spanning before and after the use of third-generation cephalosporins (3GCs) using a gene-sharing network approach. The plasmids included 82 conjugative, 22 mobilizable and 9 non-transferable plasmids and 3 P-like bacteriophages. ESBL-encoding genes were found on 64 conjugative, 6 mobilizable, 2 non-transferable plasmids and 2 P1-like bacteriophages, indicating that these last three types of mobile elements also play a role, albeit modest, in the diffusion of the ESBLs. The network analysis showed that the plasmids clustered according to their genome backbone type, but not by origin or period of isolation or by antibiotic-resistance type, including type of ESBL-encoding gene. There was no association between the type of plasmid and the phylogenetic history of the parental strains. Finer scale analysis of the more abundant clusters IncF and IncI1 showed that ESBL-encoding plasmids and plasmids isolated before the use of 3GCs had the same diversity and phylogenetic history, and that acquisition of ESBL-encoding genes had occurred during multiple independent events. Moreover, the bla CTX-M-15 gene, unlike other CTX-M genes, was inserted at a hot spot in a bla TEM-1 -Tn 2 transposon. These findings showed that ESBL-encoding genes have arrived on wide range of pre-existing plasmids and that the successful spread of bla CTX-M-15 seems to be favoured by the presence of well-adapted IncF plasmids that carry a Tn 2-bla TEM-1 transposon.